Production of poly-γ-glutamic acid by a thermotolerant glutamate-independent strain and comparative analysis of the glutamate dependent difference. (December 2017) - Zeng, Wei; Chen, Guiguang; Guo, Ye; Zhang, Bin; Dong, Mengna; Wu, Yange; Wang, Jun; Che, Zhiqun; Liang, Zhiqun
Abstract Poly-γ-glutamic acid (γ-PGA) is a promising microbial polymer with wide applications in industry, agriculture and medicine. In this study, a novel glutamate-independent γ-PGA producing strain with thermotolerant characteristics was isolated and identified asBacillus subtilis GXG-5, then its product was also characterized. The fermentation process was optimized by single-factor tests, and results showed that high temperature (50 °C) was especially suitable for the γ-PGA production by GXG-5. The γ-PGA yield reached 19.50 ± 0.75 g/L with substrate conversion efficiency of 78% at 50 °C in 10 L fermentor. Comparison of GXG-5 and GXA-28 (glutamate-dependent strain) under respective optimal fermentation conditions, the γ-PGA yield of GXG-5 was 19.0% higher than that of GXA-28, and GXG-5 was also superior to GXA-28 in the availability of carbon sources and substrates. Furthermore, the glutamate dependent difference between GXA-28 and GXG-5 was analyzed by genomic sequencing, results indicated that genes related to the glutamate dependent difference mainly involved in carbohydrate transport and metabolism and amino acid metabolism, and 13 genes related to γ-PGA synthesis were mutated in GXG-5. This study provided a potential glutamate-independent strain to replace glutamate-dependent strain for γ-PGA production, and shared novel information for understanding the glutamate dependent difference at the genomic level.